2003
DOI: 10.1046/j.1365-2265.2003.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for and prevalence of thyroid disorders in a cross‐sectional study among healthy female relatives of patients with autoimmune thyroid disease

Abstract: The high prevalence of evidence for autoimmune thyroiditis at baseline supports the importance of genetic factors in its pathogenesis. The co-occurrence of Hashimoto's thyroiditis and Graves' disease within one family suggests a common genetic basis for these diseases. Oestrogen use is associated with a lower risk, and pregnancy with a higher risk for developing hyperthyroidism. The positive correlation between TPO antibody titres and TSH levels in euthyroid subjects suggests that TPO antibodies are indeed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
7
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(147 citation statements)
references
References 28 publications
11
125
7
3
Order By: Relevance
“…Estrogen has been shown to be lower in smoking women and the use of oral contraceptives or estrogen has been associated with a lower frequency of GD (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has been shown to be lower in smoking women and the use of oral contraceptives or estrogen has been associated with a lower frequency of GD (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, estrogen usage negatively correlated with the presence of TPO antibodies (83). During the menstrual cycle, lower levels of estrogens during menstruation and luteal phase and higher levels of estrogens during the follicular phase lead to a shift from Th1-to Th2-mediated immunity respectively (84).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Vestergaard et al (25) found that ever having used OCs was associated with a slightly lower risk of Graves'disease but not of Hashimoto's disease. In a cohort study of 803 subjects at risk of developing AITD, Strieder et al (26) found that the use of oestrogen was negatively correlated with the presence of TPO-Ab. In a follow-up study of healthy middle-aged women, Massoudi et al (27) found no difference in antibody level in postmenopausal women using HRT compared with women who did not (27).…”
Section: Odds Ratiomentioning
confidence: 99%